Who Take Naps? Self-Reported and Objectively Measured Napping in Very Old Women. (18th February 2017) - Leng, Yue; Stone, Katie; Ancoli-Israel, Sonia; Covinsky, Kenneth; Yaffe, Kristine
Abstract: Background: Despite the widespread belief that napping is common among older adults, little is known about the correlates of napping. We examined the prevalence and correlates of self-reported and objectively measured napping among very old women. Methods: We studied 2, 675 community-dwelling women (mean age 84.5 ± 3.7 years; range 79–96). Self-reported napping was defined as a report of regular napping for ≥1 hour per day. Individual objective naps were defined as ≥5 consecutive minutes of inactivity as measured by actigraphy and women were characterized as "objective nappers" if they had at least 60 minutes of naps per day. Results: Seven percent of the women only had self-reported napping, 29% only had objective napping, and 14% met the criteria for both. Multinomial logistic regression showed that the independent correlates of "both subjective and objective napping" were age (per 5 year odds ratio [OR] = 1.59; 95% CI: 1.31–1.93), depressive symptoms (per SD of score, OR = 1.53; 1.32–1.77), obesity (OR =1.93; 1.42–2.61), current smoking (OR = 3.37; 1.56–7.30), heavier alcohol drinking (OR = 0.49; 0.34–0.71), history of stroke (OR = 1.56; 1.08–2.26), diabetes (OR = 2.40; 1.61–3.57), dementia (OR = 3.31; 1.27–8.62), and Parkinson's disease (OR = 7.43; 1.87–29.50). Besides, having objective napping alone was associated with age and diabetes, whereas subjective napping was associated with stroke and myocardial infarction. These associations were independent of nighttime sleep duration and fragmentation. Conclusions: Daytime napping is very common in women living in their ninth decade and both subjective and objective napping were significantly related to age and comorbidities. Future studies are needed to better understand napping and its health implications.